2019
DOI: 10.3390/foods9010009
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Rice Flour, Glutinous Rice Flour, and Tapioca Starch on the Functional Properties and Quality of an Emulsion-Type Cooked Sausage

Abstract: This study aimed to investigate the impact of the addition of rice flour (RF) and glutinous rice flour (GRF) in comparison with tapioca starch (TS) on the emulsion stability, water states, protein secondary structure, and microstructure of an emulsion-type cooked sausage. Their incorporation significantly increased the cooking yield and moisture retention of cooked sausages (p < 0.05). RF and GRF significantly decreased the fat loss and total fluid release of the cooked sausage compared to control (p < 0.05). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 26 publications
3
7
0
1
Order By: Relevance
“…The addition of 4% ST provided the greatest moisture retention with only 5% of available moisture lost after the sample compression. In fact, several authors have pointed out that starch expands during gelatinization and interacts with protein gel in the meat system to form a strong network that enhances WHC 36,37 . This could explain why ST has the highest numerical WHC value and the lowest EF value.…”
Section: Resultsmentioning
confidence: 99%
“…The addition of 4% ST provided the greatest moisture retention with only 5% of available moisture lost after the sample compression. In fact, several authors have pointed out that starch expands during gelatinization and interacts with protein gel in the meat system to form a strong network that enhances WHC 36,37 . This could explain why ST has the highest numerical WHC value and the lowest EF value.…”
Section: Resultsmentioning
confidence: 99%
“…Pereira et al investigated the effect of rice flour, glutinous rice flour, and tapioca starch on the stability of emulsion, moisture, protein secondary structure and the microstructure of cooked emulsified sausage. The study showed that among these exchangers replacing 15% of the fat content, tapioca starch had the greatest influence on the emulsion stability and cooking yield, and it contributed to greater firmness and more compact structure of the gel network [ 54 ]. Similarly, Rezler et al [ 24 ] conducted a study to investigate how the substitution of fat with modified starch affected the quality of pork liver pâtés.…”
Section: Resultsmentioning
confidence: 99%
“…[ 52 ]. Even though their main usage has been for the development of functional meat products [ 53 , 54 , 55 , 56 ], there has been also some research about the use of these ingredients as meat substitutes/extenders. Research about the use of cereals, tubers and fruits as meat extenders in the last thirteen years is summarised in Table 2 .…”
Section: Meat Extendersmentioning
confidence: 99%